To the problem of life duration increase of drilling units crown block pulleys - Червинский, Владимир Петрович; Дихтяренко, Константин Викторович; Пупышев, Андрей Игоревич (Eastern-European Journal of Enterprise Technologies, 2012)
The problems of increase the life duration of crown block pulleys and drill rigs traveling blocks due to special thermoplastic synthetic inserts, a pair of "pulley-rope” are considered